ANALISIS MENURUNNYA KARAKTER DAN NILAI MORAL SISWA SEKOLAH DASAR DI SDN MERAPI 1 - Etri Septia Rahma; Fahrani Nur Fadhillah; Suherli Kusmana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The decline in the character and moral values of elementary school students is an increasingly urgent concern, which can be seen from the decline in discipline, the use of less polite language, and the weakening of honesty in daily life at school. This study aims to describe the character condition and moral values of students at SDN Merapi 1, identify the factors that cause the decline, and examine the role of teachers, parents, and schools in strengthening character education. This study used a descriptive qualitative approach by involving the principal, one homeroom teacher, parents, and twenty-five students of class V as informants. Data were collected through interviews, written reflection sheets, and documentation studies, then analyzed using the Miles and Huberman model which included data reduction, data presentation, and conclusion drawn. The results of the study show that most students still show positive characters, such as discipline coming on time, respect for teachers, honesty, empathy for friends, and concern for the school environment. However, it was found that there was a tendency to decline in language discipline and politeness in a small number of students, most of whom were influenced by family conditions, social environment, and uncontrolled use of gadgets. This study concludes that the character formation of elementary school students in general is still relatively good, but it still requires continuous cooperation between schools, teachers, and families, especially in supervising the use of gadgets and strengthening consistent habituation, so that there is no further deterioration in character and morals in students.